Can trainees design and deliver a national audit of epistaxis management? A pilot of a secure web-based audit tool and research trainee collaboratives. Issue 6 (23rd March 2017) - Mehta, N; Williams, R J; Smith, M E; Hall, A; Hardman, J C; Cheung, L; Ellis, M P; Fussey, J M; Lakhani, R; McLaren, O; Nankivell, P C; Sharma, N; et al.
Abstract: Objective: To investigate the feasibility of a national audit of epistaxis management led and delivered by a multi-region trainee collaborative using a web-based interface to capture patient data. Methods: Six trainee collaboratives across England nominated one site each and worked together to carry out this pilot. An encrypted data capture tool was adapted and installed within the infrastructure of a university secure server. Site-lead feedback was assessed through questionnaires. Results: Sixty-three patients with epistaxis were admitted over a two-week period. Site leads reported an average of 5 minutes to complete questionnaires and described the tool as easy to use. Data quality was high, with little missing data. Site-lead feedback showed high satisfaction ratings for the project (mean, 4.83 out of 5). Conclusion: This pilot showed that trainee collaboratives can work together to deliver an audit using an encrypted data capture tool cost-effectively, whilst maintaining the highest levels of data quality.